PERFORMANCE AND EMISSION ANALYSIS OF CONSTANT SPEED SI ENGINE OPERATED ON HYTHANE (HCNG) - Yadav, Bhupesh; Soni, Shyam; Sharma, Dilip; Sharma, Pushpendra (MATTER: International Journal of Science and Technology, 2017)
Energy is the basic need of human to survive in this dynamic world. The whole world is toiling hard to meet its energy demands. Every country in this world has high energy demand owing to its increasing population which is posing a threat to energy sustainability. Generally, Energy is consumed in Agriculture, Residential and Transportation sector in which transportation sector has a high percentage of energy consumption. Conventional fuels which are used to power vehicles are having limited reserves. In the present scenario, Petroleum reserves are depleting at a faster rate and causing environmental pollution. It has inspired the researchers to develop new alternate fuels. Alternate fuels are having significant energy content and lower emissions as compared to conventional fuels. Alcohol, Biodiesel, Liquefied Petroleum Gas (LPG), Compressed Natural Gas (CNG) and Hydrogen are the alternate fuels which are being used today. CNG is being used extensively all over the world. CNG is having low laminar burning velocity which makes it more prone towards knocking. Hydrogen has high laminar burning velocity which makes it a better supplement to CNG. The blend thus obtained by mixing Hydrogen and CNG is known as Hythane or HCNG. Hythane has the advantages of both the parent fuels which make it a promising fuel for automotives. This paper includes the effect of Hydrogen addition to CNG which is tested on a single cylinder, four-stroke, water cooled SI engine. Determination of optimum percentage of Hydrogen in CNG and emissions analysis is also included in the paper.